Acceleration of the Rate of Silver Nanoparticle Formation Using Microbubbles in a Sonochemical Process. Issue 3 (4th March 2017) - Iizuka, Atsushi; Takeda, Satoshi; Kumagai, Kazukiyo; Yanagisawa, Yukio; Yamasaki, Akihiro
Abstract : The effect of the addition of microbubbles on the formation of silver nanoparticles produced in an ultrasonic radiation-mediated process was investigated. The addition of microbubbles with an area-based median diameter of 26.0 µm and a bubble volume density of 0.18 cm 3 /L significantly increased the silver nanoparticle formation rate during the sonochemical process. The size distribution of the silver nanoparticles was largely unaffected by the addition of the microbubbles. The influence of changes in the microbubble volume density on the formation of the silver nanoparticles was also investigated; it was confirmed that the rate of formation of the silver nanoparticles increased moderately with increasing volume density. The gradient in absorption spectra was approximately 30 times larger for the case when microbubbles (median diameter: 28.3 µm) were added at 0.74 cm 3 /L, compared with the case without microbubbles. The results suggested that the microbubbles provided reaction sites similar to cavitation bubbles in the ultrasonic reaction.